Knowledge, Attitude, and Practices Regarding Adult Immunization among Postgraduate Resident Doctors in MGM Hospital, Navi Mumbai, India - Nishank Chandrapal Kashyap; Rakesh Maruti Thamke; Aditi Tayade Singhania (Journal of Public Health and Primary Care)
Introduction: Adult immunization is an important but neglected health-care service. The adult population needs to keep their vaccination up to date because immunity provided through childhood vaccines weans off eventually making the adult and elderly prone to acquiring some of the vaccine-preventable diseases. Objectives: The objectives of this study were to assess the knowledge of postgraduate resident doctors regarding recommended adult vaccination. Materials and Methods: A cross-sectional study was conducted among 261 postgraduate resident doctors of tertiary care medical institutions in Navi Mumbai. Participants were selected on the basis of eligibility criteria those who gave consent for the study. Prestructured and pretested questionnaires were used to assess the participants and their knowledge regarding adult immunization based on Centers for Disease Control and Prevention Guidelines(recommended vaccines for adults, others recommended vaccines based on age, life events such as pregnancy/international traveler/health care workers/immigrants, and health conditions). Results and Conclusion: About 27.6% of resident doctors did not even know that an adult immunization schedule exists. The best known to them were COVID-19 (98.3%, i.e. 57 residents) and hepatitis B vaccine (82.8%, i.e. 42 residents). Some of the special conditions were known to them, i.e. Td or TdaP during pregnancy. The lack of knowledge and practices were clearly observed during the study among postgraduate resident doctors. To implement and execute this idea of universal health coverage through the Universal Immunization Program, resident doctors must have basic knowledge regarding the adult immunization schedule. Primary care physicians and general public need to be more aware of the benefits and availability of adult vaccination.